The capability of village devices in stunting prevention in Nagan Raya District - Susy Sriwahyuni; Safrizal Safrizal; Darmawan Darmawan; Danvil Nabela; Ridha Ilham; Teuku Muliadi (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Indonesia is the second highest contributor to stunting in Southeast Asia, so prevention is necessary to reduce the prevalence of stunting to the maximum. One of the efforts that can be made is to establish synergy between the government and the community and strengthen capacity building for village officials. This study aims to see the ability of village officials to prevent stunting in the Nagan Raya District. This descriptive-analytic research method with a cross-sectional design was conducted in April 2021. The population consists of 220 villages in Nagan Raya District. The sampling technique used the cluster sampling technique so that 12 villages were obtained with 96 respondents. They are collecting data using a questionnaire instrument. The test in this study used logistic regression for bivariate analysis and multiple logistic regression for multivariate analysis. The results showed that there was a significant relationship between increasing the capability of village officials and the variable level of education (p= 0,040; OR= 2,77), knowledge (p= 0,001; OR= 7,22) implementers (p= 0,002; OR= 8,54) and manager (p= 0,001; OR= 11,05). The conclusion is that there is a significant relationship between the variables of education, knowledge, implementers, and managers. There is no significant relationship between the variables of age, income, and training with the ability of village officials to prevent stunting.